A study of the prevalence of preoperative anaemia and iron deficiency in adult elective surgical patients in hospitals in the western cape province, South Africa. “A multicentre prospective observational study of the prevalence of preoperative anaemia and iron deficiency in adult elective surgical patients in hospitals in western cape province, South Africa.” - Conradie, Willem Stephanus (Department of Anaesthesia and Perioperative Medicine, 2022)
Background. Preoperative anaemia has been shown to be an independent risk factor for postoperative morbidity and mortality. Iron deficiency is the leading cause of anaemia globally. There are limited data describing the burden of perioperative anaemia and the relative contribution of iron deficiency in South Africa (SA). Objectives. To determine the prevalence and severity of preoperative anaemia in adults presenting for elective surgery in Western Cape Province, SA, and to investigate the contribution of iron deficiency as a cause of the anaemia. For this purpose, an investigative protocol from a recent consensus statement on the management of perioperative anaemia was applied. Methods. We performed a prospective, observational study in adult patients presenting for elective non-cardiac, non-obstetric surgery over a 5-day period at six Western Cape government-funded hospitals. The World Health Organization patient classification was applied, and patients with anaemia were investigated for iron deficiency. Results. The prevalence of preoperative anaemia was 28% (105/375; 95% confidence interval (CI) 23.5 - 32.5); 55/105 patients (52%) had moderate and 11/105 (11%) severe anaemia. Iron deficiency was the cause of anaemia in 37% (32/87; 95% CI 26.6 - 46.9), but only 9% of irondeficient patients received iron supplementation prior to surgery. Conclusions. Preoperative anaemia was common in this study, and more than half of the affected patients had moderate to severe anaemia. Iron deficiency was responsible for almost 40% of cases. Iron supplementation was under-utilised in the preoperative period as a means of increasing haemoglobin. The introduction of system-wide policies would empower perioperative physicians to mitigate the risk associated with preoperative anaemia in the Western Cape.